2020
DOI: 10.3390/nu12030876
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Nutrition Interventions in Vending Machines to Encourage the Purchase and Consumption of Healthier Food and Drinks in the University Setting: A Systematic Review

Abstract: University food environments typically offer an abundance of unhealthy foods, including through vending machines. This review evaluated the effectiveness of nutrition interventions in vending machines in the university setting. Ten databases were searched for experimental studies published up to July 2019, evaluating nutrition interventions that aimed to encourage the purchase or consumption of healthier foods and drinks in vending machines in the university setting. In total, 401 articles were identified, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…Differently from findings shown in a recent systematic review, in which university food environments are potentially contributing to inadequate dietary intakes, and overweight/obesity risk [ 32 ], our study showed that most of the low-income students with adequate weight present adequate dietary intake regarding TEI, macronutrients, and iron. However, they presented inadequate intake regarding sodium, calcium, and cholesterol.…”
Section: Discussioncontrasting
confidence: 99%
“…Differently from findings shown in a recent systematic review, in which university food environments are potentially contributing to inadequate dietary intakes, and overweight/obesity risk [ 32 ], our study showed that most of the low-income students with adequate weight present adequate dietary intake regarding TEI, macronutrients, and iron. However, they presented inadequate intake regarding sodium, calcium, and cholesterol.…”
Section: Discussioncontrasting
confidence: 99%
“…A systematic review of VM nutrition interventions at university settings concluded that effective interventions involve providing healthier VM replacement, reducing the prices of healthier items, and promoting them through awareness campaigns [ 15 ]. Increasing the availability of healthy products with and without additional nutrition communication at a university in Italy nudged the consumers’ food choices towards healthy options [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that engagement with young people is essential for transformation and meaningful change due to their in uence and insight into contemporary issues 16,17 . Many studies have previously assessed this topic with a singular approach, including an audit without student consultation or qualitative consultations without a comprehensive assessment of the environment 18,19,20,21,22 . The current study utilised a combined approach to holistically assess the university food environment.…”
Section: Discussionmentioning
confidence: 99%